The Conopidae of Costa Rica (Diptera) (Part 1: Conopinae – Conopini &Tropidomyiini) - Stuke, Jens-Hermann; Skevington, Jeffrey H. (Zootaxa, 2007)
The first part of a Conopid faunal review for Costa Rica presents data for 25 species from the Conopinae (tribes Tropidomyiini and Conopini). Two hundred and eighty-five specimens have been examined and identified. Physocephala herrerai spec. nov. and Physoconops zumbadoi spec. nov. are new to science. Sixteen species are reported the first time for the country. We introduce the following taxonomic changes: Physoconops (Gyroconops) ocellatus (Giglio-Tos, 1892) is a valid species [status rev.]; Physoconops rufipennis (Macquart, 1844) belongs to the subgenus Pachyconops Camras, 1955 [status rev.]; Physoconops gracilianus Camras, 1955 is a junior synonym of Physoconops pallifrons (Coquillett, 1904) [syn. nov.]. Keys for the species of the genera Physocephala Schiner, 1861 and Physoconops Szilady, 1926 are presented. Most species are illustrated with photo plates.